Exploring COVID-19 stress and its factors in Bangladesh: A perception-based study - Islam, S.M. Didar-Ul (Heliyon, 2020)
BACKGROUND: The COVID-19 pandemic has aggregated mental health sufferings throughout the entire world. Suicide completions are the extreme consequences of COVID-19 related psychological burdens, which was reported in many countries including Bangladesh. However, there are lack of study assessing COVID-19 related human stress and its’ associations with other relevant factors affecting quality of life in the country, and which were explored in the present study. METHODS: An online based survey was carried out among 340 Bangladeshi adult populations (65.90% male; mean age 26.23 ± 6.39) by utilizing the socio-demographics, possible human stress due to COVID-19 pandemic and its consequences. Dataset were analysed through a set of statistical tools e.g., T-test, one-way ANOVA, Pearson's Correlation Matrix (PCM), Principal Component Analysis (PCA), and Cluster Analysis (CA). RESULTS: About 85.60% of the participants are in COVID-19-related stress, which results in sleep shortness, short temper, and chaos in family. Fear of COVID-19 infection (i.e., self and/or family member(s), and/or relatives), hampering scheduled study plan and future career, and financial difficulties are identified as the main causes of human stress. Results of PCM explain the relationship among the factors of human stress, and found economic hardship and food crisis are linked together causes stress of mass people, while hamper of formal education and future plan create stress of career seeker. T-test, and one-way ANOVA illustrate demographic characteristics (i.e., occupation, age, gender, and marital status) have significant effects on elevated mental stress. Moreover, PCA and CA results revealed significant interface among the respondents’ perception and factors of human stress, which matched with the existing scenario of the country. CONCLUSIONS: Considering the present findings, it is essential to introduce time-oriented policy, and implement care monitoring plans in the country, which may help in managing the pandemic as well as nurturing the public mental health to combat COVID-19 related psychological challenges.